7-19j+11j=2(-13j+13)+19j

Simple and best practice solution for 7-19j+11j=2(-13j+13)+19j equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-19j+11j=2(-13j+13)+19j equation:


Simplifying
7 + -19j + 11j = 2(-13j + 13) + 19j

Combine like terms: -19j + 11j = -8j
7 + -8j = 2(-13j + 13) + 19j

Reorder the terms:
7 + -8j = 2(13 + -13j) + 19j
7 + -8j = (13 * 2 + -13j * 2) + 19j
7 + -8j = (26 + -26j) + 19j

Combine like terms: -26j + 19j = -7j
7 + -8j = 26 + -7j

Solving
7 + -8j = 26 + -7j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '7j' to each side of the equation.
7 + -8j + 7j = 26 + -7j + 7j

Combine like terms: -8j + 7j = -1j
7 + -1j = 26 + -7j + 7j

Combine like terms: -7j + 7j = 0
7 + -1j = 26 + 0
7 + -1j = 26

Add '-7' to each side of the equation.
7 + -7 + -1j = 26 + -7

Combine like terms: 7 + -7 = 0
0 + -1j = 26 + -7
-1j = 26 + -7

Combine like terms: 26 + -7 = 19
-1j = 19

Divide each side by '-1'.
j = -19

Simplifying
j = -19

See similar equations:

| V=w*l*h | | 27-2x=16+9x | | .0625x=4.5 | | 2y-8y+3=9 | | -3(-10c+5)=c-2(-16c-3) | | 2x-7=11fory | | 3(x-8)=3x | | 18y=3(9y+3) | | 6k-(7-6k)=-89 | | x-(-26)=6 | | 5x+8y+6=0 | | 2(14.75x)+2(14.75)=50 | | 6(8n+5)=-3(-18n-6) | | 12m+9=2m-11 | | 3(p+3)=-7p+39 | | 2(14.5x)+2(14.5)=50 | | 3x-3=-204 | | 11h-13=4(9h+17)+19 | | -8-x=x-3x | | 4(2+w)=35 | | -6+17=4-8+y | | 6-7x=7x-10x+4 | | 2(15.75x)+2(15.75)=50 | | R=6(a+b) | | -99.533753=3.839(4.7a-0.5) | | 2(16x)+2(16)=50 | | 6x-5x+3=10-17 | | 159+2h=955 | | x-40=-32 | | 6x+3(x+11)=96 | | x=yw+z | | 5n+7=7n+7-2n |

Equations solver categories